Implementation Of Tax Planning As An Effort To Reduce Company Income Tax Liabilities (Case Study Of Pt X) - Regina Nadya Wira Shaharani; Iqbal, Syaiful (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to give some tax planning alternative schemes that could be implemented at PT X to save its corporate income taxes. This study uses a qualitative approach with PT X’s financial report for 2022 and 2023 as research objects. This study results on three tax plan alternative schemes that minimize corporate income taxes of PT X. The first scheme is done by changing PT X’s inventory valuation method, from FIFO to the average method. The second scheme is done by maximalizing software amortization costs which have never been calculated. The third scheme is done by allocating employee allowance cost to scholarship program on corporate social responsibility cost. The combined-strategy scheme is done by implementing three strategies in every scheme all at once. These schemes are compared to determine the best tax-saving recommendation using the tax retention rate calculation. As the calculation result the best scheme to implement by PT X is combined-strategy scheme with its tax retention rate of 89%.